2005
DOI: 10.1300/j013v42n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Emotion Regulation and Relationships with Perceived Health in Patients with Rheumatoid Arthritis

Abstract: ABSTRACT. Emotion regulation has been associated with perceived health in rheumatoid arthritis, which is diagnosed three times more often in women than men. Our aim was to examine gender differences in styles of emotion regulation (ambiguity, control, orientation, and expression) and gender-specificity of the associations between emotion regulation and perceived health (psychological well-being, social functioning, physical functioning, and disease activity) in 244 female and 91 male patients with rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…As an alternative comparison sample, future research could recruit control patients who are seeking health care for another (pain) condition, as care seeking has been found to be predicted by a number of psychosocial variables that may differentiate our current patient and control samples. The findings cannot be generalized to other ethnicities, male subjects, or patients with fibromyalgia not diagnosed according to the American College of Rheumatology criteria, which are variables related to emotional experiencing and regulation [43,44]. Finally, this study is limited by the use of self-report questionnaires to measure constructs and by its cross-sectional nature, which prevents causal inferences.…”
Section: Discussionmentioning
confidence: 91%
“…As an alternative comparison sample, future research could recruit control patients who are seeking health care for another (pain) condition, as care seeking has been found to be predicted by a number of psychosocial variables that may differentiate our current patient and control samples. The findings cannot be generalized to other ethnicities, male subjects, or patients with fibromyalgia not diagnosed according to the American College of Rheumatology criteria, which are variables related to emotional experiencing and regulation [43,44]. Finally, this study is limited by the use of self-report questionnaires to measure constructs and by its cross-sectional nature, which prevents causal inferences.…”
Section: Discussionmentioning
confidence: 91%
“…This is consistent with Chaplin et al (2008)'s finding that greater subjective negative emotion was correlated with stress- and alcohol-cue-related alcohol cravings in males but not in females. Several studies have indicated that women tend to acknowledge and value experiencing emotions compared to men, who tend to be more avoidant of emotions (e.g., Nolen-Hoeksema, 2000; Thayer et al, 2003; van Middendorp et al, 2005). Given that classic cognitive theories of psychopathology state that cognition drives the experience of emotion (see Alloy & Riskind, 2005), it could be that men avoid processing these negative cognitions and instead drink in order to cope with these distressing thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in reports of negative feelings could also be due to gender differences in reporting. One study (van Middendorp et al, 2005) reported that women with RA valued emotions in daily life more than men with RA and reported the experience of emotions more intensely.…”
Section: Quality Of Lifementioning
confidence: 99%